Assessing the Hydropower Potential Using Hydrological Models and Geospatial Tools in the White Bandama Watershed (Côte d'Ivoire, West Africa) - Kouadio, Claude Alain; Kouassi, Kouakou Lazare; Diedhiou, Arona; Obahoundje, Salomon; Amoussou, Ernest; Kamagate, Bamory; Paturel, Jean-emmanuel; Coulibaly, Talnan Jean Honoré; Coulibaly, Houebagnon Saint Jean Patrick; Didi, Regis Sacre; Savane, Issiaka (Frontiers in Water, 2022)
An assessment of hydropower potential at the watershed scale was conducted at the White Bandama Watershed (WBW) in Côte d’Ivoire (West Africa). The method used involves the application of a hydrological model (Soil and Water Assessment Tool [SWAT]) coupled with a Quantum Geographic Information System (QGIS), denoted as QSWAT, to assess the water resource availability and hydropower potential of streams and determine potential hydropower sites for future hydropower development in the watershed. Geospatial data about the topography, soil types, land use/land cover, weather, and discharge were considered in hydrological and hydrogeomorphological characterization of the watershed. Streamflow and climate data-enabled model operation and simulation of the hydrology of the watershed. The model performance and robustness were confirmed with the p-factor, r-factor, coefficient of determination R², and Nash–Sutcliffe (NS) efficiency coefficient. The hydropower potential of streams was evaluated in considering the simulated streamflow and water head. A total of 22 future hydropower sites was identified, geolocated, and classified with an estimated total production capacity of 538.56 MW.